Types and development pathways of lateral line scales in some teleost species. (8th November 2011) - Voronina, Elena P.; Hughes, Dianne R.
Abstract Voronina, E.P. and Hughes, D.R. 2011. Types and development pathways of lateral line scales in some teleost species. —Acta Zoologica (Stockholm) 00: 1–13. A comparative study of lateral line scales (lls) in nine teleost species was undertaken to trace their ontogenetic structural changes. Three universal characters were used to describe and classify definitive and developing lls. The four main structural types in teleosts are represented. In adult fish, lls are the same structural type in all parts of lateral line in any one specimen, but number of tubules and their orientation may vary. In juvenile fish, except for one species, the structural type of every lls changes with growth, and this process progresses along the lateral line in the direction of development typical for the species. Definitive structural type of the lls is not determined by common scale type and size, presence or absence of nerve foramen on lls, scale overlapping or time of initiation of scales and trunk canal. Development pathways are proposed in which terminal states correspond to the final development of the most complex lls type in Cyprinus carpio, Carassius carassius, Oncorhynchus mykiss, Diplodus annularis and Mullus barbatus. The intermediate states of these pathways correspond to other types of lls as examples of pedomorphosis in Perca fluviatilis, Sander lucioperca, Symphysodon aequifasciatus and Hippoglossoides platessoides.